SPARE PARTS STOCK MANAGEMENT: a case study to reduce machine downtime in a metallurgical industry - Janfrone, Alexandre Spolaor; Campos, Ronaldo Ribeiro de (Revista Interface Tecnológica, 2020)
The advancement of technology and the search for product transformation processes with quality and lower cost are hot topics in all industrial scope. The use of technology and improvement management to optimize results is one of the factors that has made companies remain competitive in the market, with one of the key points being the inventory management process. This process can become a generator of savings and meeting customer deadlines, but it can also retain too many financial resources and without much use. Through a practical analysis it will be possible to report the feasibility of investment and positive impacts on business results based on data. Within this principle, the stock of spare parts is a determining factor in the area of industrial maintenance, being the objective of the present work, demonstrating through a case study its effectiveness in a metallurgy company in the interior of the State of São Paulo.